Taking 200 mg Vitamin C Three Times per Day Improved Extraction Socket Wound Healing Parameters: A Randomized Clinical Trial - Nanthanut Pisalsitsakul; Chaiwat Pinnoi; Narueporn Sutanthavibul; Paksinee Kamolratanakul (International Journal of Dentistry)
Vitamin C is essential for wound healing. However, there are no reports concerning the effect of a different dose of vitamin C on extraction wound size clinically. Therefore, the aim of this study was to investigate the effect of different oral vitamin C doses on extraction wound healing. A split-mouth, double-blind randomized clinical trial was performed in 42 patients who underwent symmetric bilateral noninfected premolar extraction. The patients were randomly divided into 3 groups, namely, P/600, P/1,500, and 600/1,500 (14 patients for each group); P/600: placebo vs. 600 mg vitamin C/d, P/1,500: placebo vs. 1,500 mg vitamin C/d, and 600/1,500: 600 mg vitamin C/d vs. 1,500 mg vitamin C/d. Patients were prescribed placebo or/and vitamin C three times a day for 10 days after each tooth extraction. Extraction wound size and pain score were evaluated. The wound assessment was performed on day 0, 7, and 21; and then the tooth on the other side was extracted using the same protocol. Pain score was recorded on the first three days after extraction. The reduced size of mesiodistal extraction wound in percentage reduction between day 0 and 7 of teeth receiving vitamin C 600 mg/d was more than that in placebo (P<0.05). Pain scores on day 1–3 of teeth receiving vitamin C 600 mg/d were significantly lower than the placebo side (P<0.05). Taking oral vitamin C 600 mg/d over three doses for 10 days after tooth extraction enhances extraction wound healing by reducing mesiodistal extraction wound and reduces postoperative pain.